Economical and easy methods of smoke stain removal from maxillofacial prostheses (Annals of Medical Research, 2022)
Aim: Service life of a maxillofacial prosthesis is too short especially because of color instability. This study aimed to investigate the effects of hand soap and chlorhexidine gluconate mouthwash on the color of maxillofacial prosthesis after exposure of cigarette smoke.Materials and Methods: Sixty specimens were fabricated from a maxillofacial silicone material. Two groups (n=20) were pigmented intrinsically mimicking dark and fair tone skin and one group was not pigmented for control. All the specimens were exposed to cigarette smoke in a closed apparatus designed for the study. Color measurements of the specimens were performed before and after smoke exposition by using a spectrophotometer. Half of all the specimens (n=30) consisting of dark, fair and non-pigmented ones was rubbed with liquid hand soap and the other half was immersed in chlorhexidine gluconate mouthwash (0.12% chlorhexidine digluconate). Color measurement was repeated after cleaning process. Color differences were calculated both CIELab (ΔE*ab) and CIEDE2000 (ΔE00) color measurement formulas.Results: Color groups had significantly different color change values in terms of ΔE00 and ΔE*ab after exposition to smoke and cleaning methods (p
Keywords: Maxillofacial prosthesis; color; smoking; chlorhexidine; soap